Impact of storage temperatures and modified atmospheres on quality of fresh-peeled garlic cloves - Tanamati, F. [UNESP]; Hong, G.; Cantwell, M. I. (Int Soc Horticultural Science, 2016)
Fresh-peeled garlic is an increasingly important product for foodservice and retail markets. Two storage tests were conducted using garlic cloves ('California Late') that were peeled and packaged commercially. In Test #1 (MAP bags of 454 g), O-2 concentrations averaged 15, 10 and 5% at 0, 5 and 10 degrees C, respectively; the corresponding CO2 concentrations averaged 8, 15 and 23%. In Test #2 with small vacuum packed bags (30 g) inside larger master packages (170 g), atmospheres in the former averaged 1.5-3% O-2 and 20-30% CO2 at all storage temperatures (0, 2.5, 5 and 7.5 degrees C), while the master bags averaged 20-21% O2 and 0.5-0.8% CO2. In both tests, discoloration occurred in areas damaged during mechanical peeling, and was associated with lower L* and increased chroma values. In Test #1, decay was a significant contributor to loss of quality. In Test #1 excellent visual quality was maintained during 21 and 16 d at 0 and 5 degrees C, respectively, and acceptable quality was maintained for about 10 d at 10C. In Test #2, very good visual quality was maintained up to 28 d at 0 and 2.5 degrees C, and acceptable quality was maintained for 21 d at 5 and 7.5 degrees C. No important changes in texture were observed due to temperature or storage time. Pungency (thiosulfinate and pyruvate concentrations) decreased with time and the decrease was greater at higher storage temperatures. A reasonable expected storage-life of commercially peeled and modified atmosphere packaged garlic is 3-4 weeks at 0 degrees C, 2-3 weeks at 5 degrees C and 1-2 weeks at 10 degrees C.
Keywords: visual appearance; color; pungency; dry weight; storage-life